Association Between Alcohol Use and Angina Symptoms Among Outpatients From the Veterans Health Administration. Issue 2 (March 2018) - Williams, Emily C.; Bryson, Chris L.; Sun, Haili; Au, David H.; Bradley, Katharine A.
Abstract : Background: Alcohol use is associated with angina incidence, but associations between alcohol use and experience of angina among patients with coronary artery disease (CAD) have not been described. Methods: Outpatients with CAD from 7 clinics in the Veterans Health Administration were surveyed; alcohol use was measured using the validated Alcohol Use Disorders Identification Test-Consumption scores categorized into 6 groups: nondrinking, low-risk drinking, and mild, moderate, severe, and very severe unhealthy alcohol use. Three domains of self-reported angina symptoms (frequency, stability, and physical function) were measured with the Seattle Angina Questionnaire. Linear regression models evaluated associations between alcohol use groups and angina symptoms. Models were adjusted first for age and then additionally for smoking, comorbidities, and depression. Results: Patients (n = 8303) had a mean age of 66 years. In age-adjusted analyses, a U-shaped association was observed between alcohol use groups and all angina outcomes, with patients in nondrinking and severe unhealthy alcohol groups reporting the greatest angina symptoms and lowest functioning. After full adjustment, no clinically important and few statistically important differences were observed across alcohol use in angina stability or frequency. Patients in the nondrinking group had statistically greater functional limitation from angina than those in all groups of unhealthy alcohol use, though differences were small. Patients in all groups of unhealthy alcohol use did not differ significantly from those with low-risk drinking. Conclusions: Alcohol use was associated with some small statistically but no clinically important differences in angina symptoms among patients with CAD. This cross-sectional study does not support a protective effect of low-level drinking on self-reported angina.